2010
DOI: 10.1212/wnl.0b013e3181cbcd5c
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic differences in antiepileptic drug prescriptions to adult epilepsy patients

Abstract: This nationwide cross-sectional study of epilepsy patients indicates that sociodemographic characteristics are important for access to neurologists and prescriptions of individual antiepileptic drugs. Prospective studies using patient-related outcomes are needed to analyze the consequences of these differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
41
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 21 publications
11
41
1
Order By: Relevance
“…The most obvious one could be socioeconomic differences which are not reflected in the type of insurance. There are definite disparities in the relative use of first-generation AEDs versus second-generation AEDs prescribed to some socioeconomic and racial groups [12,13]. Another explanation for the apparently greater benefit of newer drugs might be greater comorbidity or more serious etiologies of epilepsy among the patients receiving older drugs, but we controlled for comorbidity by using the Charlson Comorbidity Index.…”
Section: Discussionmentioning
confidence: 99%
“…The most obvious one could be socioeconomic differences which are not reflected in the type of insurance. There are definite disparities in the relative use of first-generation AEDs versus second-generation AEDs prescribed to some socioeconomic and racial groups [12,13]. Another explanation for the apparently greater benefit of newer drugs might be greater comorbidity or more serious etiologies of epilepsy among the patients receiving older drugs, but we controlled for comorbidity by using the Charlson Comorbidity Index.…”
Section: Discussionmentioning
confidence: 99%
“…Pricing may also be an issue, and the prescribing trends suggest that those patients traditionally less likely to be able to afford brand name are less likely to receive one. A 2010 study by Mattsson et al found that certain sociodemographic factors of patients with epilepsy were linked to access to a specialist—these factors included being young and having a higher income [22]. This suggests that patients with epilepsy who are elderly and have lower incomes are less likely to have access to a specialist and, possibly, brand name AEDs.…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of this study, patients with occurrence of any of ICD-10-codes G40, G41, or R56.8 more than 7 days after the stroke index date were classified as PSE. The positive predictive value of the epilepsy diagnosis in the NPR is not known, but the register is frequently used to identify epilepsy in register-based research [13, 14]. Causes of death in Sweden are reported in text on a death certificate by a physician and coded as International Classification of Disease (ICD)-10 codes by the National Board of Health and Welfare according to the instruction in the ICD-10 manual.…”
Section: Methodsmentioning
confidence: 99%